Detention and its discontents: punishment and compliance within the U.K. detention estate through the lens of the withdrawal of Assisted Voluntary Return. Issue 13 (3rd October 2019) - Walker, Sarah
ABSTRACT: Detention centres and return programmes are increasingly important instruments of border control across Europe. In 2014, the U.K. Home Office removed Assisted Voluntary Return (AVR) from detention, meaning it is no longer available to detainees. Drawing on both secondary data analysis of interviews with welfare staff in an Immigration Removal Centre (IRC) and Home Office senior managers and primary data from follow-on interviews with welfare staff and NGO workers, the paper analyses the Home Office rationale behind this withdrawal. Using this policy change as a lens reveals how through a responsibilisation discourse inherent in Home Office policy the subject of the 'detainee' is criminalised and framed as non-compliant and thus undeserving of 'privileges', such as AVR, in an increasingly punitive space. In contrast, both welfare officers and NGO workers frame detainees in a more nuanced, sometimes contradictory, manner; recognising the role of the state in creating vulnerabilities. By examining how dominant forms of discrimination are held in place by the banal ways categories are repeated in everyday discourse, this paper highlights the increasing pathologisation of deviance and framing of detainees as criminal 'other'. As such it contributes to debates on the contradictory world of detention and the sociology of punishment.